Global Burden Attributable to High Low-Density Lipoprotein-Cholesterol From 1990 to 2019 - Du, Heyue; Shi, Qingyang; Song, Peige; Pan, Xiong-Fei; Yang, Xueli; Chen, Lingmin; He, Yazhou; Zong, Geng; Zhu, Ye; Su, Baihai; Li, Sheyu (Frontiers in Cardiovascular Medicine, 2022)
Background High low-density lipoprotein-cholesterol (LDL-C) is a public health issue contributing to ischemic heart disease (IHD) and stroke. Method In this ecological study, we collected summary exposure values (SEVs), deaths, disability-adjusted life of years (DALYs), and Social Demographic Index (SDI) of high LDL-C from 1990 to 2019 using the query tool from the Global Burden of Disease (GBD) Collaborative Network. Outcomes include SEVs, deaths, and DALYs attributable to high LDL-C stratified by sex, age, region, SDI, countries, and territories. Estimated annual percentage changes (EAPCs) were applied to estimate annual trends of changes in these outcomes. We applied the weighted segmented regression with break-point estimation to detect the linear piecewise relationship between SDI and high LDL-C disease burden. Results Globally, 3.00 million (95% uncertainty interval [UI], 2.35–3.76 million) people in 1990 and 4.40 million (95% UI, 3.30–5.65 million) people died from high LDL-C in 2019. The absolute annual burden from deaths and DALYs attributed to high LDL-C increased by 46% (95% UI, 35–56%) and 41% (95% UI, 31–50%) from 1990 to 2019. The age-standardized SEV, death, and DALY was decreased by 9% (95% UI, −11 to −8%), 37% (95% UI, −41−33%), and 32% (95% UI, −37 to −28%), respectively, during the study period. There was a negative association between SDI and high LDL-C-related age-standardized death and DALY rates when SDI surpassed 0.71 and 0.71, respectively. Conclusion Although the overall age-standardized burden of high LDL-C is controlled in the past 30 years, it remains increasing in moderate SDI countries, and decreasing trends are disappearing in high SDI countries. New challenges require new actions stratified by countries with different SDI levels.